2003
DOI: 10.1046/j.1525-1438.2003.13019.x
|View full text |Cite
|
Sign up to set email alerts
|

CA125 levels are a weak predictor of optimal cytoreductive surgery in patients with advanced epithelial ovarian cancer

Abstract: The utility of preoperative CA125 to predict optimal primary tumor cytoreduction in patients with advanced (stages IIIC and IV) epithelial ovarian cancer is controversial. In this paper, we retrospectively review patients with stage IIIC and IV epithelial ovarian cancer who underwent primary cytoreductive surgery from 1989 to 2001. Ninety-nine patients were identified and included in the analysis. All patients had preoperative CA125 levels measured. Operative and pathology reports were reviewed. Optimal cytore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Although their overall optimal cytoreduction level was 45%, 73% of patients with a CA 125 level Ͻ 500 underwent optimal cytoreduction. In contrast, only 22% of 24,25 In contrast, Memarzadeh et al 26 published an investigation of 99 patients with advanced ovarian carcinoma. With a relatively high overall optimal resection rate of 73%, they found that the preoperative CA 125 level was a poor predictor of optimal resection.…”
Section: Discussionmentioning
confidence: 99%
“…Although their overall optimal cytoreduction level was 45%, 73% of patients with a CA 125 level Ͻ 500 underwent optimal cytoreduction. In contrast, only 22% of 24,25 In contrast, Memarzadeh et al 26 published an investigation of 99 patients with advanced ovarian carcinoma. With a relatively high overall optimal resection rate of 73%, they found that the preoperative CA 125 level was a poor predictor of optimal resection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaanalysis concluded that although a CA-125 > 500 U/mL was a strong risk factor for suboptimal debulking, it lacked the accuracy to independently predict surgical outcome. [34][35][36][37][38] In our study, it was found that almost equal number of patients (around 70 and 74.9%%) underwent optimal cytoreduction in both groups i.e., <500IU/ml and >500IU/ml. The value of CA125 did not correlate with optimal cytoreduction with P value -0.721 which is statistically not significant.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, in other studies preoperative serum CA125 level was not found to be a reliable predictor of optimal cytoreduction. [20][21][22][23][24][25] Several studies included data regarding low preoperative CA125 levels (<100 U/mL) in the assessment of the ability to predict optimal cytoreduction and outcome. Vorgias et al 26 found that all of 19 patients with CA125 levels of <100 U/mL were optimally cytoreduced.…”
Section: Discussionmentioning
confidence: 99%